Análises dos efeitos do óleo da semente de açaí (Euterpe oleracea Mart.) em modelo de colite/câncer colorretal - WOLFF, Laís Araújo Souza (2025)
Introduction: Euterpe oleracea Mart. (açaí) is an Amazonian palm tree rich in bioactive compounds with potential antioxidant, anti-inflammatory, and antitumor properties. Colorectal cancer (CRC), one of the most prevalent malignancies, has a high mortality rate. Although açaí has been studied for its beneficial effects in various conditions, there are still gaps regarding its potential role in the prevention and treatment of colorectal cancer. Objective: This study aims to evaluate the chronic toxicity and pharmacological effects of açaí seed oil (Euterpe oleracea Mart.) in an experimental model of colitis-associated colorectal cancer. Material and Methods: The fruit of E. oleracea Mart. was collected in October 2022 at Parque da Juçara (São Luís, Maranhão, Brazil) and stored frozen until processing. The pulp and fiber were removed, and the seed was macerated using a knife mill to obtain a powder, followed by oil extraction using the Soxhlet method. The fatty acid profile was identified through Gas Chromatography-Mass Spectrometry (GC-MS) after oil esterification. For the in vivo chronic toxicity assays, 10 Swiss mice (5 males and 5 females) received 1000 mg/kg/day of the oil orally for 90 days, following the OECD guideline N408, with adaptations. Feed consumption and body weight were monitored. After euthanasia, blood samples were collected for hematological analyses, and organs (liver, kidneys, spleen, and uterus) were examined both macroscopically and histopathologically. In the colitis/colorectal cancer model, 28 Swiss mice were divided into four groups: negative control and three preventive groups (100, 300, and 1000 mg/kg of oil, orally, daily). Preventive treatment started 30 days prior to colorectal cancer induction with a single dose of 10 mg/kg Azoxymethane (AOM, intraperitoneally), followed by three cycles of Dextran Sodium Sulfate (DSS, 2.0% ad libitum for 5 days, interspersed with two weeks of water). After induction, animals were monitored for 50 days, followed by an additional 20 days of treatment with the aforementioned oil doses. Feed intake and body weight progression were monitored throughout the experiment. After euthanasia, the colon was analyzed for the presence and number of tumor polyps, and fragments were separated for myeloperoxidase (MPO) activity and total glutathione (GSH) level analysis. Additionally, the liver, kidneys, spleen, and colon were weighed and subjected to macroscopic and histopathological examination. The study was approved by the Animal Ethics Committee (CEUA-UFMA) under protocol number 23115.035913/2023-50.Results: Ten compounds were identified in the E. oleracea seed oil, comprising saturated fatty acids (54.78%) and unsaturated fatty acids (44.81%). GC-MS analysis identified the major components as: (i) oleic acid (24.97%), myristic acid (23.75%), palmitic acid (19.88%), and linoleic acid (18.36%). Regarding the toxicity of the oil at 1000 mg/kg, no hematological or histopathological alterations were observed. In the colitis/colorectal cancer model, time-dependent weight gain was significant during the treatment period. Organ weight analysis revealed significant differences compared to the negative control in the liver (300 mg/kg group, p = 0.0269), kidneys (300 mg/kg group, p = 0.0477), spleen (300 mg/kg group, p = 0.0196), and colon (1000 mg/kg group, p = 0.0361). Lymphoid organ cellularity did not show statistically significant changes among groups. A significant reduction in the relative weight-to-length ratio of the colon was observed in the 1000 mg/kg preventive group (p = 0.0499) compared to the negative control. MPO activity did not significantly change; however, GSH levels increased, particularly in the 1000 mg/kg group, suggesting a possible antioxidant effect. Histopathological analysis showed preserved colonic mucosa in the control group, while the 100 mg/kg and 1000 mg/kg groups exhibited adenomas and invasive adenocarcinomas, as well as hepatic hyperplasia and renal alterations. The 300 mg/kg group showed mononuclear infiltration in the colon but also evidence of mucosal regeneration. Conclusion: Preliminary results on the effect of E. oleracea oil showed no toxicity at the highest tested concentration and tissue regeneration in the 300 mg/kg preventive group. These findings suggest that its bioactive components may influence tumor progression, highlighting the need for further studies to elucidate its mechanisms of action.